First principles investigation of graphitic carbon nitride (GCN) monolayer embedded with transition metals (Ni, Pd, and Pt) as a NO sensor - Poudel, Guna Nidhi; Shrestha, Pitamber; Rijal, Narayan Prasad; Sharama, Shri Ram; Pradhan Joshi, Leela; Parajuli, Rajendra (BIBECHANA, 2025)
Adsorption of nitric oxide on Ni, Pt, and Pd-embedded graphitic carbon nitride (GCN) has been studied computationally using density functional theory. Transition metal (TM) embedded in GCN exhibits significantly higher adsorption energy compared to pristine GCN. This study finds that Pt-embedded GCN shows a high adsorption energy of -4.560 eV, which is greater than that of other TM-embedded GCNs. While NO gas showed physisorption on the pristine GCN, it exhibited strong chemisorption on the TM-embedded systems. When functional transitional metals are embedded on its surface, along with the adsorption of NO, new energy states are introduced near the Fermi surface, which modifies the electronic properties of the system. Also, the changes in the band states of the system are noticed. Furthermore, non-magnetic GCN is found to be magnetic when Pt is embedded in it.